Hidradenitis Suppurativa Recurrence in a Caesarean Scar - K. M. Darch; T. L. Holland; L. J. Spelman (Case Reports in Obstetrics and Gynecology)
Hidradenitis suppurativa (HS), also known as acne inversa, is a chronic, relapsing inflammatory skin condition characterised by the presence of painful nodules, abscesses, and sinus tracts or scarring. Affecting up to 4% of the population, it is not uncommon and is seen predominantly in females at a ratio of 3 : 1. HS carries a substantial burden for those who suffer from it, from the significant psychosocial impact, to the cost of the multitude of topical and systemic treatments which often do not successfully control its symptoms. In this case report, we discuss a 33-year-old female known to our clinic, who presented with a recurrence of her HS in a caesarean scar, with otherwise silent disease. From our review of the literature, this appears to be only the second case of recurrence of HS in a caesarean scar reported to date. With a predilection for females of reproductive ages, involvement of sensitive areas, and an average of greater than seven years from onset of symptoms until diagnosis, the ability to recognise HS and ensure referral for specialist management is essential for all who are regularly involved in the management of this patient group.